Given:
System of equation is given as
![\begin{gathered} 3x+4y=4 \\ -x-3y=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/swn3cri78zx8t791vuczu1oenx6pb00vhd.png)
Required:
Solve system of equation by using the method elimination.
Step-by-step explanation:
By using the elimination method
we multiply second equation with 3 and then add in first equation
because by doing this process we eliminate the x
![\begin{gathered} 3x+4y+3(-x-3y)=4+3*7 \\ 3x+4y-3x-9y=4+21 \\ -5y=25 \\ y=-5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/cahzj0tx23p5o742omjopnupwmyjrpyteq.png)
now put the value of y in first equation
![\begin{gathered} 3x+4(-5)=4 \\ 3x-20=4 \\ 3x=20+4 \\ 3x=24 \\ x=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/7tx764iooz4h1jo9a6dd2ike2bnvcb6lyx.png)
Final answer:
Solution of given system of equation is (8,-5)